Rice postharvest technology in Vietnam (Nông nghiệp, 2014)
Conten: Overview of rice post harvest situation in the world and in Viet Nam; Paddy harvesting; Paddy drying; Paddy storage; Rice milling; Paddy rice quality; Paddy seed quality; Laser controlled land leveling; Economic calculations for postharvest machinery; Business models and business plans